PENGARUH LATIHAN MULTIBAL TERHADAP KEMAMPUAN PUKULAN BACKHAND PADA ATLET TENIS MEJA PTM MANDIRI PANDAU - Marbun, Surya Espas; Slamet, Slamet; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstaract: The purpose of this study was to determine whether there is an effect of multiball training on the ability of backhand punches in PTM Mandiri Pandau table tennis athletes. There are also training methods that can improve your backhand skills, Multiball practice. The form of this research is (using a one group pretest-posttest design approach) with the population of PTM Mandiri Pandau athletes, the data in this study are the entire population of 5 people. The instrument used in this study was to use a backboard test, which aims to determine the effect of multiball training on the ability of backhand punches on PTM Mandiri Pandau table tennis athletes. After that, the data is processed statistically, to test normality using the lilifours test at a significant level of 0.05?. The hypothesis proposed is that there is an effect of multiball training on the ability of backhand punches on PTM Mandiri Pandau table tennis athletes. . Based on the analysis of the normality of the data X, it produces a Lhitung of 0.1977 and a Ltable of 0.337, meaning that Lhitung <Ltable. while the Y variable yields Lhitung 0.1949 and Ltable 0.337. This means Lhitung <LTabel. Based on statistical data analysis, there is an average variable X 27.4 and an average variable Y of 37.2, then the data is normally distributed. Thus it can be concluded that for the effect between variable x and variable y, the value of t = 4.78 then tcount> ttable is (4.78)> (2.132), then Ha is accepted, in other words there is a significant effect on the effect of multiball training Against Backhand Ability on PTM Mandiri Pandau Table Tennis Athletes.Key Words:Multiball Practice, Backhand